RELATIONSHIP BETWEEN THE RANDOM BLOOD GLUCOSE LEVELS DURING ADMISSION AT EMERGENCY ROOM WITH CLINICAL OUTPUT IN ACUTE ISCHEMIC STROKE PATIENTS - Munir, Badrul; Rasyid, Harun Al; Rosita, Rizky (Malang Neurology Journal, 2015)
Background. High blood glucose level occurs on 20-50% acute ischemic stroke patients. Hyperglycemia can worsen neurology disorder of patients.Objective. To find out the relationship between random blood glucose level and clinical outcome on patients with acute ischemic stroke measured with NIHSS.Methods. Observational using stroke registry of acute ischemic stroke patients. There are 38 patients involved in this research.Results. Using Spearman shows an insignificant correlation between random blood glucose level and NIHSS output (p=0.548). However, random blood glucose level and NIHSS input shows a significant correlation (p=0.011). The result of Chi-Square test on correlation between random blood glucose level and NIHSS output shows an insignificant correlation (p=1), in contrast, random blood glucose level and NIHSS input and improvement shows a significant correlation (p=0.024 and p=0.047).Conclusion. There is no correlation between random blood glucose level at initial care and clinical outcome on patients suffering acute ischemic stroke. However, normal random blood glucose level shows had better improvement and they had tendency to get better outcome.